Natural Gas Hydrates in Flow Assurance - Sloan D. Dendy; Koh C. Carolyn; Sum A. K. Amadeu; Ballard A. L. Adam; Creek J. Jefferson; Eaton M. Michael; Lachance J. Jason; MCMullen N. Norm; Palermo T. Thierry; Shoup G. George; Talley L. Larry (Amsterdam, Elsevier, 2011)
Заглавие с титульного экрана